Differential pulse adsorptive stripping voltammetric determination of nifedipine in drug by using hanging mercury drop electrode - Phuong, Nguyen Thi Kim; Huyen, Tran Truong (Vietnam Journal of Chemistry, 2012)
Nifedipine is a calcium - channel antagonist drug used in the management of angina pectoris and hypertension through inhibition of calcium influx. A simple, rapid, and selective differential pulse adsorptive stripping voltammetric method based on reduction of an aromatic nitro group in the drug onto hanging mercury drop electrode, that has been developed for the determination of nifedipine. The analytical parameters effect the electrode reduction process have been studied such as pH, accumulation time, accumulation potential, pulse amplitude, frequency, temperature. The results show that: at pH 4; accumulation time to obtain maximum current is 30s, 120s and 300s for 10-6 M, 10-7 M and 10-8 M, respectively; pulse amplitude 50 mV; sweep rate 12.5 mV/s. The peak current showed a linear relationship with concentration in the range 10-8M - 10-7 M. The method was applied succesfully for the direct determination of nifedipine in drugs.